Effects of omega-3 fatty acids supplementation on lipids and pregnancy outcomes in pregnant women - Weijing Wang; Cai Liu; Mei Wang; Xue Wei; Lu Jiang; Fang Wang (The Journal of Maternal-Fetal & Neonatal Medicine)
Objectives To assess the impact of Omega-3 fatty acid supplementation on maternal blood lipid profiles and pregnancy outcomes.Methods This study retrospectively analyzed data from pregnant women with previous pregnancy loss and infertility, divided participants into an intervention group (n = 60) and a control group (n = 218) based on the use of Omega-3 fatty acid supplements during pregnancy, compared blood lipids between the two groups, and analyzed the effect of Omega-3 fatty acids on pregnancy outcomes.Results After a 5-week intervention with Omega-3 fatty acids, significant reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-c) levels were observed. Significant decreases in hemoglobin count and platelet count were identified after pharmacological intervention, and no significant changes in liver and kidney function or coagulation function were found in the participants. There were no statistically significant differences in the incidence of live births, pregnancy loss, preterm birth, hypertensive disorders of pregnancy, oligohydramnios, macrosomia, gestational weeks of delivery, and birth weight of newborns between the two groups.Conclusions Omega-3 fatty acid supplementation during pregnancy significantly reduced TG and had no significant negative effect on pregnancy outcomes.